1991
DOI: 10.1159/000147165
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Microscopic Study of the Parathyroid Gland of Epinephrine-Treated Golden Hamsters Subjected to Hypergravity Environment

Abstract: The ultrastructure of the parathyroid glands of golden hamsters subjected to 5-gravity environment after administration of epinephrine was studied. In the epinephrine-treated animals exposed to a hypergravity environment, the Golgi complexes associated with numerous prosecretory granules were significantly increased compared with those of the control centrifuged and epinephrine-treated animals as well as the cisternae of the granular endoplasmic reticulum compared with those of the control and centrifuged anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
5
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
(32 reference statements)
3
5
0
Order By: Relevance
“…In the PTG of the 1.2G group the rER had significantly increased cornpared with that of the control group. These findings were fairly consistent with the observations which indicated an increase in function of the PTG of animals exposed to centrifugation (Shoumura et aL, 1988(Shoumura et aL, , 1989a(Shoumura et aL, , 1989b(Shoumura et aL, , 1991a(Shoumura et aL, , 1991b(Shoumura et aL, , 1992a(Shoumura et aL, , 1992b(Shoumura et aL, , 1992c. In the present study, in the PTG of the Mg-1.2G group the Golgi apparatus and the rER have significantly increased compared with those of the Mg group and appeared to increase compared with those of the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the PTG of the 1.2G group the rER had significantly increased cornpared with that of the control group. These findings were fairly consistent with the observations which indicated an increase in function of the PTG of animals exposed to centrifugation (Shoumura et aL, 1988(Shoumura et aL, , 1989a(Shoumura et aL, , 1989b(Shoumura et aL, , 1991a(Shoumura et aL, , 1991b(Shoumura et aL, , 1992a(Shoumura et aL, , 1992b(Shoumura et aL, , 1992c. In the present study, in the PTG of the Mg-1.2G group the Golgi apparatus and the rER have significantly increased compared with those of the Mg group and appeared to increase compared with those of the control group.…”
Section: Discussionsupporting
confidence: 92%
“…In a series of recent morphological studies on the parathyroid glands (PTG) in this laboratory using centrifugation, animals were exposed to simulated increase in body weight by centrifugation at 5.0 G for 1 or 5 hr and these studies have showed acute effects of the high rotation of centrifugation on the PTG (Shoumura et aL, 1988(Shoumura et aL, , 1989a(Shoumura et aL, , 1989b(Shoumura et aL, , 1991a(Shoumura et aL, , 1991b(Shoumura et aL, , 1992a(Shoumura et aL, , 1992b(Shoumura et aL, , 1992cUtsumi et al, 1993). In addition, Sannes and Hayes (1975) have shown the effect of centrifugation at 2.0 G for 60 days on the ultrastructure of the PTG.…”
mentioning
confidence: 99%
“…The present study demonstrated that in the Mg group the serum calcium level also showed a significant decrease in comparison with the control group. Furthermore, in the parathyroid glands of the 5G group the Golgi complexes and cisternae of the granular endoplasmic reticulum appeared to be increased and lipid droplets were significantly increased as compared to those of the control group, as observed in the parathyroid glands indicating increased functional activity in golden hamsters exposed exposed to a hypergravity environment (Shoumura et al, 1988a(Shoumura et al, , 1989a(Shoumura et al, , 1989bIsono et al , 1990;Shoumura et al , 1990Shoumura et al , , 1991aShoumura et al , , 1991bShoumura et al , , 1992aShoumura et al , , 1992bShoumura et al , , 1992c.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, ultrastructural reports have dealt with the problem on the influence of a hypergravity environment on the parathyroid gland (Sannes and Hayes, 1975; Shoumura et at., 1988a, 1989a, 1989b; Isono et al, 1990; Shoumura et al, 1990Shoumura et al, , 1991aShoumura et al, , 1991bShoumura et al, , 1992aShoumura et al, , 1992bShoumura et al, , 1992c.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that lysosomes in PTG increase in number with growth, and may function in the regulation of overproduced secretory granules 10) . Our findings are generally consistent with the observations described above.…”
Section: Discussionmentioning
confidence: 99%